Factors Associated with the Utilization of the Birth Waiting House in Fakfak Tengah District, Fakfak Regency - Halibi, Maria Suzana; Azam, Mahalul; Rahayu, Sri Ratna (Public Health Perspective Journal, 2022)
The birth waiting house is one of the efforts to bring pregnant and maternity mothers access closer to health services. As forThere are various factors that become obstacles to the use of RTK, one of which is the behavior of the community which is less related to the use of the birth waiting house. The purpose of this study is to analyzethe relationship between perceptions, reference groups, resources, and socio-culture with the use of the birth waiting house in Fakfak Tengah District, Fakfak Regency. This research is an analytic survey research with a cross sectional approach. The population of this study were all mothers who gave birth in January to December 2020, totaling 226 mothers.The sample that was successfully obtained as a whole was 215 respondents,The sampling technique used is total sampling based on predetermined inclusion and exclusion criteria. The research instrument used is a questionnaire. The data analysis in this study were univariate analysis (frequency distribution), bivariate analysis (rank Spearman correlation test) and multivariate analysis (ordinal logistic regression test). The results showed that there was a significant relationship between perceptions, reference groups, resources and socio-culturewith the use of a birth waiting house in Fakfak Tengah District, Fakfak Regency.Resource and socio-cultural variables are the factors with the strongest relationship with the use of a birth waiting house in Fakfak Tengah District, Fakfak Regency.